PERBEDAAN PENGGUNAAN MEDIA VIDEO DENGAN LEAFLET TERHADAP TINGKAT PENGETAHUAN SISWA MENGENAI CUCI TANGAN PAKAI SABUN (Studi Kasus di SDN Banyuanyar 1 Sampang Tahun 2018) - Devi Ekawati HF; Suprijandani .; Ngadino . (Poltekkes Kemenkes Surabaya, 2018)
Disposable hand-washing soap (CTPS) is used to reduce the microorganisms with the techniques of flow of clean water into the palm of the hand using soap. CTPS serves to eliminate/reduce microorganism that attaches on both hands to prevent diarrheal diseases, cholera, intestinal worms, and hepatitis a. Data obtained from clinics in 2016 of 1095 and in 2017 of 1374 it these show that there is a growing number of diarrhea sufferers. The results of a survey conducted to 10 students who were given a questionnaire there are 4 students who learned of the CTPS. The purpose of this research is to know the difference between video media with leaflets about the level of knowledge of students for the CTPS SD class IV and class V.The type of this research is research pre experimental research design with one group pretest posttest design. The sample in this research as much as 72 students, while for sampling techniques is Proportional Stratified Random Sampling. Data collection procedure that is done to find out the level of knowledge of students using a questionnaire. Furthermore the data that has been collected is analyzed with statistical tests is Exact Fisher.The results of the measurement of the level of knowledge of students before intervention in either category of 27.78% (10 students). Whereas after intervention by using video media of 58.33% (21 students). And media use leaflet before intervention by 25% and after the intervention of 83.33% in both categories. Fisher's exact test results obtained results of 0.034 0.05. So there is a difference in the use of video media with leaflets for the student's level of knowledge regarding the CTPS (P 0.05). It is recommended students can obtain information about CTPS from multiple sources and get learning material with media leaflets. Keywords: CTPS, Media, Level of Knowledge